The given expression is
![f(x) = \frac{3(x+2}{(x+2)(x+6)}](https://tex.z-dn.net/?f=%20f%28x%29%20%3D%20%5Cfrac%7B3%28x%2B2%7D%7B%28x%2B2%29%28x%2B6%29%7D%20)
And since we have x+2 common in numerator and denominator, there is a hole at x+2=0, that is at x=-2
And a function is undefined when denominator is zero. And at x=-6, denominator become zero.
So, at x=-6, the function is undefined, or there is a vertical asymptote at x=-6 and hole at x=-2 .
Answer:
=
Step-by-step explanation:
v8 + 3 = 8 + v3
-3 -3
________________
v8 = 5 + v3
-v3 -v3
___________
v5 = 5
The second one should be the answer
Answer:
3/8 cups
Step-by-step explanation:
divide 3/4 by two